Gastrointestinal dysfunction after spinal cord injury - Holmes, Gregory M. (Exp Neurol, 2019)
The gastrointestinal tract of vertebrates is a heterogeneous organ system innervated to varying degrees by a local enteric neural network as well as extrinsic parasympathetic and sympathetic neural circuits located along the brainstem and spinal axis. This diverse organ system serves to regulate the secretory and propulsive reflexes integral to the digestion and absorption of nutrients. The quasi-segmental distribution of the neural circuits innervating the gastrointestinal (GI) tract produces varying degrees of dysfunction depending upon the level of spinal cord injury (SCI). At all levels of SCI, GI dysfunction frequently presents life-long challenges to individuals coping with injury. Growing attention to the profound changes that occur across the entire physiology of individuals with SCI reveals profound knowledge gaps in our understanding of the temporal dimensions and magnitude of organ-specific co-morbidities following SCI. It is essential to understand and identify these broad pathophysiological changes in order to develop appropriate evidence-based strategies for management by clinicians, caregivers and individuals living with SCI. This review summarizes the neurophysiology of the GI tract in the uninjured state and the pathophysiology associated with the systemic effects of SCI.